2004
DOI: 10.1128/mcb.24.12.5521-5533.2004
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Regulation of Poly(A) Nuclease

Abstract: With rare exceptions, mRNAs whose synthesis originates within nuclei contain a 3Ј poly(A) tail. Poly(A) tracts are not encoded within genes but are added to nascent pre-mRNAs in a processing reaction that involves site-specific cleavage and subsequent polyadenylation (11,16,40,42). In Saccharomyces cerevisiae, newly synthesized poly(A) tails of different transcripts are relatively homogeneous, with their final lengths determined by the combined actions of poly(A) polymerase holoenzyme (Pap1p and Fip1p), poly(A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 41 publications
5
102
0
Order By: Relevance
“…While ATX2 binds the PABC domain itself, the major interaction site of Pbp1 with Pab1 appears to be a region preceding the PABC domain of Pab1. 28 The observed different binding modes of ATX2 and Pbp1 to PABC point to common evolutionary changes of the protein binding interface and are consistent with the fact that ATX2 contains the PABC-interacting motif PAM2, but not Pbp1. In agreement with that, we could not observe an interaction of human ATX2 and the corresponding region of the yeast PABP homolog Pab1 in the yeast-2-hybrid system (data not shown).…”
Section: Atx2 Interacts With the C-terminal Domain Of Pabpsupporting
confidence: 55%
See 3 more Smart Citations
“…While ATX2 binds the PABC domain itself, the major interaction site of Pbp1 with Pab1 appears to be a region preceding the PABC domain of Pab1. 28 The observed different binding modes of ATX2 and Pbp1 to PABC point to common evolutionary changes of the protein binding interface and are consistent with the fact that ATX2 contains the PABC-interacting motif PAM2, but not Pbp1. In agreement with that, we could not observe an interaction of human ATX2 and the corresponding region of the yeast PABP homolog Pab1 in the yeast-2-hybrid system (data not shown).…”
Section: Atx2 Interacts With the C-terminal Domain Of Pabpsupporting
confidence: 55%
“…44 We also included the recently described interactions of Pbp1 with Mkt1, Pan2, Fir1, Ufd1, Dig1, and the as yet uncharacterized protein Pbp4 in the network. [27][28][29] We observed that the putative nuclease Mkt1 and the poly(A)-nuclease subunit Pan2 not only interact directly with Pbp1, but are also linked to Pbp1 indirectly via other interaction partners. This may point to larger protein complexes containing Pbp1 and Mkt1 or Pan3 and other proteins.…”
Section: Analysis Of Pbp1 Functionsmentioning
confidence: 85%
See 2 more Smart Citations
“…25 Further evidence supporting a functional role of Pab1 in mRNA biogenesis is the accumulation of polyadenylated mRNAs in the nucleus of pan2 and pan3 deletion mutants, 25 which code for two subunits of a deadenylase complex (PAN) recruited by Pab1. 30 Because the PAN complex is thought to participate in the last step of mRNA biogenesis, 31 these results suggest that Pab1 is involved in the final step of 3' end processing before mRNA export.…”
Section: Nuclear Role Of Pabpc1mentioning
confidence: 98%